Executive Committee Minutes 2007-02-01 - Academic Senate:::::::::
EMT Hiring, Faculty Eligible for Emeritus Status, Faculty Eligible for Emeritus Status, AMCS curriculum changes, Resolution endorsing the Statewide Resolution on the Importance of Settling the Contract between CFA and the CSU